Workplace Bullying And Work Engagement Among Hotel Employees In Pakistan: The Roles Of Psychological Well-Being, Work Meaningfulness And Psychosocial Safety Climate - Anwar, Aizza (2023)
This study designed an integrative model using the job demand (JD-R) theory and conservation of resource (COR) theory to examine the impact of bullying, both face-to-face and online, on the work engagement of hotel employees. Secondly, it investigates the mediating role of psychological well-being between workplace bullying, workplace cyberbullying, and work engagement. The mediating role of workplace meaningfulness between psychological well-being and work engagement is also tested. This study also recognizes the importance of a safety climate in the hotel industry, thus examining the moderating role of the psychosocial safety climate between workplace bullying, cyberbullying, and psychological well-being.